2006
DOI: 10.1002/gps.1692
|View full text |Cite
|
Sign up to set email alerts
|

QUALIDEM: development and evaluation of a dementia specific quality of life instrument––validation

Abstract: The results of this validation study together with the obtained content validity through the method of construction provide sufficient support for validity of the QUALIDEM to be used for care evaluation and research in residential settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(213 citation statements)
references
References 29 publications
(27 reference statements)
8
197
0
8
Order By: Relevance
“…There has been a movement in QoL toward the measurement of the experience of the person, including usually perceptions or satisfactions with psychological, physical, and social domains (Ettema et al, 2005b). In dementia-specific HRQL instruments, the measurement is also aimed at capturing the experience of the person with dementia.…”
Section: Conceptualization and Operationalizationmentioning
confidence: 99%
“…There has been a movement in QoL toward the measurement of the experience of the person, including usually perceptions or satisfactions with psychological, physical, and social domains (Ettema et al, 2005b). In dementia-specific HRQL instruments, the measurement is also aimed at capturing the experience of the person with dementia.…”
Section: Conceptualization and Operationalizationmentioning
confidence: 99%
“…(2) The Quality of Life Alzheimer's Disease scale (QoL-AD) is a self-report questionnaire including 13 items, each one rated on a 1-4 Likert scale, which can be completed both by patients with mild to moderate dementia and by informal caregivers, and yields a single score which weights patient's score twice as much as [Brod et al 1999] QoL-AD [Logsdon et al 2002] DEMQOL [Smith et al 2005] CBS [Ready et al 2002] ADRQL [Rabins et al 1999] DS-DAT [Hurley et al 1992] Vienna List [Porzsolt et al 2004] Qualidem [Ettema et al 2007 [Rabins et al 1999]. (6) The Discomfort Scale -Dementia of Alzheimer Type (DS-DAT) encompasses nine behavioral indicators of discomfort in patients with severe dementia and language disorders, rated by professional caregivers [Hurley et al 1992].…”
Section: Introductionmentioning
confidence: 99%
“…The QUALIDEM is an observational instrument, and the reliability and validity are satisfactory [11,27] . The scale includes 37 items describing observable behavior with four possible responses to how often this behavior has been observed in the past week, ranging from never to almost daily.…”
Section: Quality Of Lifementioning
confidence: 99%
“…For instance, Thomas et al [3] and Bostrom et al [4] found a significant lower QoL in community-dwelling people with Lewy body dementia compared to Alzheimer dementia (AD). Furthermore, increased cognitive impairment and the presence of neuropsychiatric symptoms (NPS) were negatively associated with QoL in both community-dwelling people and nursing home residents with dementia [2,3,[5][6][7][8][9][10][11][12][13] . Of the NPS studied, especially depression was strongly associated with lower QoL scores [5,[7][8][9][10][11][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%